Seeking revenge or seeking reconciliation? How concern for social‐image and felt shame helps explain responses in reciprocal intergroup conflict. (10th November 2017) - Gausel, Nicolay; Leach, Colin Wayne; Mazziotta, Agostino; Feuchte, Friederike
Abstract: In conflicts with reciprocal violence, individuals belong to a group that has been both perpetrator and victim. In a field experiment in Liberia, West Africa, we led participants ( N = 146) to focus on their group as either perpetrator or victim in order to investigate its effect on orientation towards inter‐group reconciliation or revenge. Compared to a perpetrator focus, a victim focus led to slightly more revenge orientation and moderately less reconciliation orientation. The effect of the focus manipulation on revenge orientation was fully mediated, and reconciliation orientation partly mediated, by viewing the in‐group's social‐image as at risk. Independent of perpetrator or victim focus, shame (but not guilt) was a distinct explanation of moderately more reconciliation orientation. This is consistent with a growing body of work demonstrating the pro‐social potential of shame. Taken together, results suggest how groups in reciprocal conflict might be encouraged towards reconciliation and away from revenge by feeling shame for their wrongdoing and viewing their social‐image as less at risk. As victims and perpetrators are widely thought to have different orientations to inter‐group reconciliation and revenge, we suggest that work on reciprocal conflicts should account for the fact that people can belong to a group that has been both perpetrator and victim.